Incidencia económica y financiera de la aplicación de las disposiciones tributarias del impuesto a la renta, impuesto al valor agregado (Iva) e impuestos a los consumos especiales en los comerciantes mayoristas de abastos del sur de Quito. Caso: Centro de acopio Mercado Mayorista de Quito. - Hernández Burgos, Lorena Paola (2011)
This thesis is a study which aims to determine the economic and financial impact of implementing the tax provisions of the tax; income, value added, special consumption in supplies wholesalers of Quito South - Wholesale Market distribution center in Quito. The area subject to this investigation, initially marketing function was wholesale consumer staples, but the economic situation generated the retail and retail, so there were also other tax obligations, same that have been evaded or circumvented by low tax culture within taxpayers.